Reappraisal of Oral Steroid Therapy for Myasthenia Gravis - Imai, Tomihiro; Suzuki, Shigeaki; Nagane, Yuriko; Uzawa, Akiyuki; Murai, Hiroyuki; Utsugisawa, Kimiaki (Frontiers in Neurology, 2020)
Treatment with oral corticosteroids at high doses with an escalation and de-escalation schedule is effective against MG. In fact, the use of corticosteroids has led to a reduction in mortality to below 10% after the 1960’s. However, long-term use of oral steroids above a certain dosage level is known to cause a number of problems. In 2014, the Japanese clinical guidelines for MG proposed that the first goal in MG treatment (treatment target) should be set at minimal manifestations (MM) with oral prednisolone (PSL) 5 mg/day or below, and that treatment strategies should strive to attain this level as rapidly as possible. In 2015, a multicenter, cross-sectional study revealed that higher PSL dose and longer PSL treatment do not ensure better outcome. In the absence of good response, the PSL dose should be decreased by combining with modalities such as plasma exchange/plasmapheresis and intravenous immunoglobulin (fast-acting treatments). In 2018, we examined the correlation between oral PSL dosing regimen and achievement of the treatment target in patients with generalized MG by conducting a multicenter, cross-sectional study with a large population of MG patients in Japan. To achieve the treatment target, odds ratios (ORs) for low-dose versus high-dose regimen were 10.4 (P<0.0001) after 1 year of treatment, 2.75 (P=0.007) after 2 years and 1.86 (P=0.15) after 3 years; and ORs for low-dose versus intermediate-dose regimen were 13.4 (P<0.0001) after 1 year, 3.99 (P=0.0003) after 2 years and 4.92 (P=0.0004) after 3 years. Early combined use of fast-acting treatments (OR: 2.19 after 2 years, P=0.02; OR: 2.11 after 3 years, P=0.04) or calcineurin inhibitors (OR: 2.09 after 2 years, P=0.03; OR: 2.36 after 3 years, P=0.02) was associated positively with achievement of the treatment target. We conclude that a low-dose PSL regimen with early combination of other treatment options may ensure earlier achievement of the treatment target in generalized MG. However, even with this regimen, approximately 35% of patients did not achieve the treatment target after 3 years. These results suggest the limitation of the current oral corticosteroid therapy. We need to develop new treatment options to increase the rate of satisfactory outcome.